Design and Development of Financial Reporting Information System for Taman Pendidikan AlQuran Governance - Achmad Asrori; I Kadek Dwi Nuryana (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The Al-Qur'an Education Park (TPQ) plays a significant role in shaping character and understanding of Islam from an early age. However, TPQ financial management is typically conducted manually, increasing the risk of recording errors, lack of transparency, and difficulties in decision-making. This study aims to develop a computerized financial reporting information system for more effective and efficient TPQ governance in accordance with the Ministry of Religious Affairs (Kemenag) standards. The prototype method is used in system development, allowing for iterative improvements based on user feedback. The system is designed to record financial transactions, generate financial reports, and present relevant financial information for TPQ administrators. System testing is conducted using the black-box method to evaluate functionality from the user’s perspective and the white-box method to examine the internal structure and logic. This study demonstrates that the financial reporting information system improves the accuracy, efficiency, and transparency of TPQ financial management in compliance with Kemenag standards. Additionally, the system facilitates financial analysis and better decision-making for administrators. Therefore, this system is expected to contribute to the overall improvement of TPQ governance.